Reduced Superficial Capillary Density in Cerebral Infarction Is Inversely Correlated With the NIHSS Score - Kwapong, William Robert; Yan, Yuying; Hao, Zilong; Wu, Bo (Frontiers in Aging Neuroscience, 2021)
Purpose: The retina and the brain share similar neuronal and microvascular features, therein we aimed to assess the structural and microvascular changes in the macula and choriocapillaris (CC) in patients with cerebral infarction when compared with healthy controls using optical coherence tomography angiography (OCTA). Methods: OCTA was used to image and measure the capillary density in the radial peripapillary capillaries (RPC), superficial capillary plexus (SCP), deep capillary plexus (DCP), choriocapillaris (CC), and mean area of the foveal avascular zone (FAZ) in all participants. Twenty-two cerebral infarction patients based on their magnetic resonance imaging (MRI) and 25 healthy controls were included in our study. Results: Density of the RPC (P < 0.001), SCP (P = 0.001), DCP (P < 0.001) and CC (P < 0.001) were significantly reduced in cerebral infarction patients when compared with healthy controls, respectively. Retinal thickness measurements (P < 0.05) were significantly reduced in cerebral infarction patients when compared with healthy controls. The mean FAZ area was significantly larger (P = 0.012) in cerebral infarction patients when compared with healthy controls. National Institute of HealthStroke Scale (NIHSS) inversely correlated with SCP density in cerebral infarction patients (Rho = −0.409, P = 0.001). Receiver operating characteristics curve analysis showed that the blood flow of the choriocapillaris had the highest index [area under the receiver operatingcharacteristic (AUROC) = 0.964] to discriminate cerebral infarction patients from the healthy controls. Conclusions: Our study suggests that cerebral microcirculation dysfunction which occurs in cerebral infarction is mirrored in the macula and choroidal microcirculation. OCTA has the potential to non-invasively characterize the macula and choroidal changes in cerebral infarction in vivo.